The longitudinal effects of resisted and assisted sprint training on sprint kinematics, acceleration, and maximum velocity: a systematic review and meta-analysis - Myrvang, S.; van den Tillaar, R. (Sports Medicine - Open, 2024)
Background Sprinting is important for both individual and team sports, and enhancing performance is often done through resisted, assisted, or combined sprint training. However, the effectiveness of these methods compared to traditional sprint training remains inconclusive. The objective of this review with meta-analysis was to review the current literature on intervention studies analyzing the effects of resisted, assisted, and combined (resisted-assisted) training on sprint kinematics and performance in terms of acceleration and maximum velocity.